The Profile of Scientific Literacy and Self-Concept in Learning Physics - Sheila Fitriana; Tuti Hardianti; Syahwin Syahwin (Jurnal Ilmiah Pendidikan Fisika, 2023)
Based on the findings of interviews and preliminary observations, there are various issues with learning physics, including the continued use of the expository approach and a reliance on the capacity to recall topics without comprehending their significance. This study aimed to characterize the profile of students' scientific literacy and self-concept. The descriptive research approach was employed in this study, with a single case design. Learning observation sheets, interview sheets, scientific literacy tests, and student self-concept surveys were utilized as study instruments. The quantitative data acquired from questionnaires and tests in this study will be examined descriptively by percentage. Students' scientific literacy abilities are still rather low in general. Competency domain indicators for explaining scientific phenomena are in the medium category, obtaining a percentage of 78%, while competency domain indicators for evaluating and designing scientific investigations are in a low category, obtaining a percentage of 58%, and competency domain indicators for interpreting data and scientific evidence are in the deficient category, obtaining a percentage of only 46%. Students' attitudes toward learning physics are rated as modest. Based on the outcomes of this study, more in-depth research utilizing appropriate learning models is required to monitor success in physics learning and develop students' scientific literacy abilities.